Variasi Perkataan Hari Kiamat Dalam Al Qur’an: Satu Tinjauan Umum - Khairul Asyraf Mohd Nathir; Mohd Sukki Othman; Wan Muhammad Wan Sulong; Nik Farhan Mustapha (Global Academic Excellence, 2024)
Volume: 2 Issues: 5